2013
DOI: 10.15690/vramn.v68i7.707
|View full text |Cite
|
Sign up to set email alerts
|

The Success of Heart Rate Variability Biofeedback Parameters in Persons With Different Levels of Blood Pressure

Abstract: Objective. The aim was to determine the nature of cardiovascular reactions during a single session of heart rate variability (HRV) biofeedback in order to increase vagal effects on heart rhythm in patients with different initial levels of blood pressure (BP). Participants and methods. 33 people with normal blood pressure (group I), 20 people with uncorrected arterial hypertension (AH) grade 1-2 (group II) and 22 people with AH grade 1-2 taking antihypertensive drugs (group III) were observed. The parameters of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Monitoring HRV is a viable alternative option for hypertension [19]. In persons with increased blood pressure, there is an aptitude to improve the total power of the heart rate variability (HRV) continuum through HRVBF for vagal cardiovascular management claim [21]. While analysis of the HRV power spectrum accounts for some physiological mechanisms [5], there are environmental factors that also play crucial roles in the progress of hypertension [29].…”
Section: Htn Hrvbf and Hrvmentioning
confidence: 99%
See 1 more Smart Citation
“…Monitoring HRV is a viable alternative option for hypertension [19]. In persons with increased blood pressure, there is an aptitude to improve the total power of the heart rate variability (HRV) continuum through HRVBF for vagal cardiovascular management claim [21]. While analysis of the HRV power spectrum accounts for some physiological mechanisms [5], there are environmental factors that also play crucial roles in the progress of hypertension [29].…”
Section: Htn Hrvbf and Hrvmentioning
confidence: 99%
“…In considering the questions espoused by this article, one needs to be cognizant of the parameters involved in both HRVBF, and HRV for a viable assessment of the sympathetic activities involved, and the effects of biofeedback [7]. Additionally, it is paramount to consider the effects of HRVBF based on its clinical outcomes (study design and comparison techniques with or without experimental or control group) in hypertension or varying levels of blood pressure [21].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, randomized control trials that either included only unmedicated outpatients or statistically controlled for the effects of antihypertensive pharmacotherapy reported significant decreases in hypertension following HRVB compared to active control (Nolan et al, 2010;Palomba et al, 2011). In addition, studies examining the nature of cardiovascular reactions following HRVB suggested that this intervention is beneficial for patients treated with antihypertensive pharmacotherapy as it leads to pronounced reactivity of vagal mechanism (Poskotinova et al, 2013). This is of particular importance given that hypertensives treated pharmacologically still display significant decreases in VM-HRV compared to normotensives (Cowan et al, 1993;Liao et al, 1996;Mussalo et al, 2001).…”
Section: Addressing Autonomic Imbalances Associated With Hypertensionmentioning
confidence: 99%